Traumatic injuries to the renal blood vessels and in-hospital renal complications in patients with penetrating or blunt trauma - Alzerwi, Nasser A. N. (Frontiers in Surgery, 2023)
Background: Traumatic injuries to renal blood vessels (IRBV) can have significant consequences for patients, impacting their mortality, morbidity, and quality of life. Objective: This study aimed to compare trauma types and injury characteristics, vital signs, and outcomes in patients with and without IRBV (nIRBV) and examine whether IRBV and pre-existing renal dysfunction affected the likelihood of in-hospital renal complications (iHRC). Materials and Methods: After identifying penetrating and blunt trauma victims with IRBV in the National Trauma Data Bank, patient demographics, injury-related variables, treatment outcomes, and deaths under care were analyzed and compared. Results: Of the 994184 trauma victims, 610 (0.6%) experienced IRBV. Victims in the IRBV group (IRBVG) had a significantly higher frequency of penetrating injuries (19.5 % vs. 9.2 %, P<0.001) and higher injury severity score (ISS ≥25, 61.5% vs. 6.7%). Most injuries in both groups were unintentional, although a higher frequency of assault was noted in the IRBVG. The incidence of iHRC was higher in the IRBVG (6.6%) than in the nIRBVG (0.4%; P<0.001). The IRBV [OR=3.5 (95% CI=(2.4-5.0))], preexisting renal disorders [OR=2.5 (95% CI=(2.1-2.9))], and in-hospital cardiac arrest [OR=8.6 (95% CI=(7.7-9.5))] were found to be among the factors associated with a higher risk of iHRC. Conclusions: IRBV and pre-existing renal disorders considerably increased the risk of developing iHRC. Due to the long- and short-term consequences of associated cardiovascular, renal, and hemodynamic complications, victims of IRBV require specialized renal management and close monitoring.